Strategies for timing nitrogen fertilization of pear trees based on the distribution, storage, and remobilization of 15N from seasonal application of (15NH4)2SO4 - Hai-bo JIANG; Hong-xu LI; Ming-xin ZHAO; Xin-lan MEI; Ya-long KANG; Cai-xia DONG; Yangchun XU (Journal of Integrative Agriculture, 2020)
In order to improve the management of nitrogen (N) fertilization in pear orchards, we investigated the effects of application timing on the distribution, storage, and remobilization of N in mature pear trees in a field experiment at Jingtai County, Gansu Province, China. Nine trees were selected for the experiment and each received equal aliquots of 83.33 g N in the autumn, spring, and summer, with 15N-labeled (NH4)2SO4 used in one of the aliquots each season. Results showed that the (15N H4)2SO4 applied in the autumn remained in the soil during the winter. In the following spring this N was absorbed and rapidly remobilized into each organ, especially new organs (leaves, fruit and new shoots). The 15N supplied in spring was rapidly transported to developing fruit between the young fruit and fruit enlargement stages. 15N from the summer application of fertilizer was mainly stored in the coarse roots over the winter, then was mobilized to support growth of new organs in spring. In conclusion, for pear trees we recommend that the autumn application of N-fertilizer be soon after fruit harvest in order to increase N stores in fine roots. Spring application should be between full bloom and the young fruit stages to meet the high N demands of developing fruit. Summer application of fertilizer at the fruit enlargement stage does not contemporaneously affect the growth of pears, but increases the N stored in coarse roots, and in turn the amount available for remobilization in spring.